Effect and Safety of Adding Metformin to Insulin Therapy in Treating Adolescents With Type 1 Diabetes Mellitus: An Updated Meta-Analysis of 10 Randomized Controlled Trials - Liu, Ying; Chen, Hongbo; Li, Hui; Li, Liman; Wu, Jin; Li, Hong (Frontiers in Endocrinology, 2022)
Background: The role of metformin in the treatment of adolescents with type 1 diabetes mellitus (T1DM) remain controversial. We conducted this updated meta-analysis to generate a comprehensive assessment regarding the effect and safety of metformin in treating adolescents with T1DM. Methods: We systematically searched PubMed, Embase, and the Cochrane Central Registry of Controlled Trials (CENTRAL) from their inception through November 2021 to identify randomized controlled trials evaluating the efficacy of metformin in the treatment of adolescents with T1DM. The primary outcome was HbA1c level, and secondary outcomes included body mass index (BMI), total insulin daily dose (TIDD) (unit/kg/d), hypoglycaemia events, diabetes ketoacidosis (DKA) events, gastrointestinal adverse events (GIAEs). Statistical analysis was conducted using RevMan 5.4 and STATA 14.0. Results: Ten studies enrolling 539 T1DM adolescents were included. Results suggested that metformin significantly decreased the HbA1c level at 12 months (mean difference [MD])=-0.50, 95% confidence interval [CI]=-0.61 to -0.39, P < 0.01), BMI kg/m2 at 3 months (MD=-1.05, 95%CI=-2.05 to -0.05, P=0.04), BMI z-score at 6 months (MD=-0.10, 95%CI=-0.14 to -0.06, P<0.01), TIDD at 3 (MD=-0.13, 95%CI=-0.20 to -0.06, P<0.01), 6 (MD=-0.18, 95%CI=-0.25 to -0.11, P<0.01), and 12 (MD=-0.42, 95%CI=-0.49 to -0.35, P<0.01) months, but significantly increased the risk of hypoglycaemia events (risk ratio [RR]=3.13, 95%CI=1.05 to 9.32, P=0.04) and GIAEs (RR=1.64, 95%CI=1.28 to 2.10, P<0.01). For remaining outcomes at other time points, no statistical difference was identified. Sensitivity analysis confirmed the robustness of all pooled results. Conclusions: The use of metformin might result in decreased BMI and TIDD but increased in risk of hypoglycemia events and GIAEs in adolescents with T1DM. However, future studies are required to further confirm the optimal dose and duration of metformin therapy.